p53 and Translation Attenuation Regulate Distinct Cell Cycle Checkpoints during Endoplasmic Reticulum (ER) Stress - Thomas, Sally E. (American Society for Biochemistry and Molecular Biology, 2013)
Cell cycle checkpoints ensure that proliferation occurs only under permissive conditions, but their role in linking nutrient availability to cell division is incompletely understood. Protein folding within the endoplasmic reticulum (ER) is exquisitely sensitive to energy supply and amino acid sources because deficiencies impair luminal protein folding and consequently trigger ER stress signaling. Following ER stress, many cell types arrest within the G(1) phase, although recent studies have identified a novel ER stress G(2) checkpoint. Here, we report that ER stress affects cell cycle progression via two classes of signal: an early inhibition of protein synthesis leading to G(2) delay involving CHK1 and a later induction of G(1) arrest associated both with the induction of p53 target genes and loss of cyclin D1. We show that substitution of p53/47 for p53 impairs the ER stress G(1) checkpoint, attenuates the recovery of protein translation, and impairs induction of NOXA, a mediator of cell death. We propose that cell cycle regulation in response to ER stress comprises redundant pathways invoked sequentially first to impair G(2) progression prior to ultimate G(1) arrest.